Reading interests of grades 4, 5, and 6 students of Diliman Preparatory School - Manalo, Charmaine A. (2009)
This study surveyed the Grades 4, 5, and 6 students of Diliman Preparatory School to determine the students' reading interests and whether their school library caters books for these interests. It also sought to find whether the students' grade levels and after-school activities have an effect on their reading interests. A total of 142 respondents answered the survey. Of these 142 respondents, 45 came from Grade 4, 46 from Grade 5, and 51 from Grade 6.